Bayesian Statistics: Foundations And Applications In Artificial Intelligence - Shradha Dwivediand Peeyush Dwivedi (Migration Letters, 2024)
This article explores the principles of Bayesian statistics and its transformative impact on artificial intelligence (AI). By integrating prior knowledge with observed data, Bayesian methods enhance model performance across various domains, from[1] machine learning to natural language processing. This paper reviews the foundational concepts, discusses computational techniques, and highlights key applications, emphasizing the benefits and challenges associated with Bayesian approaches.